Analyzing EU's Agricultural Sector and Public Spending under Climate Change - Dinca Gheorghita; Netcu Ioana - Catalina; El-Naser Asmaa (Sustainability, 2024)
Climate change not only affects weather conditions, patterns, and the frequency and severity of extreme weather events but also changes the structure of government spending. Agriculture is an important sector of the European Union (EU). However, by 2050, the industry will most likely decrease by 16%. One-third of the EU's budget has been spent on agricultural funding, adaptation, and climate action. The effect of climate change on agriculture is mixed and dependent on the location of the region. The southern EU is adversely affected, while the northern EU is positively affected by the changes in weather patterns. The main goal of this paper is to gain insight regarding the effect climate change has on public spending in relation to the agricultural sector of the EU, using the pooled Ordinary Least Squares (OLS) and Generalized Method of Moments (GMM) methodology. The study concludes that public spending is influenced by government expenditure and government support in agricultural research and development in the EU region. In the southern EU region, the variables impacting public spending are greenhouse gases from the agricultural sector, temperature, and GDP, while in the northern region, no variable has a significant impact on public spending proxied by agricultural subsidies. The policy recommendations include a better allocation of agricultural subsidies, reconsideration of the efficiency of Common Agricultural Policy (CAP), and a focus on expanding investment in research and development in the agricultural sector.
Keywords: economic growth; climate change; global warming; public budget; Generalized Method of Moments (GMM)